Does an Over-Connected Visual Cortex Undermine Efforts to Stay Sober After Treatment for Alcohol Use Disorder? - Muller, Angela M.; Meyerhoff, Dieter J. (Frontiers in Psychiatry, 2020)
A fine-tuned interplay of highly synchronized activity within and between the brain’s communities is a crucial feature of the brain’s functional organization. We wanted to investigate in individuals with alcohol use disorder (AUD) the degree to which the interplay of the brain’s community-architecture and the extended brain reward system (eBRS) is affected by drinking status (relapse or abstinence). We used Graph Theory Analysis of resting-state fMRI data from treatment seekers at one month of abstinence to model the brain’s intrinsic community configuration and their follow-up data as abstainers or relapsers three months later to quantify the degree of global across-community interaction between the eBRS and the intrinsic communities at both timepoints. After one month of abstinence, the ventromedial PFC in particular showed a significantly higher global across-community interaction in the 22 future relapsers when compared to 30 light/non-drinking controls. These differences were no longer present three months later when the relapsers had resumed drinking. We found no significant differences between abstainers and controls at either timepoint. Post hoc tests revealed that one eBRS region, the ventromedial PFC, showed a significant global across-community interaction with a community comprising the visual cortex in relapsers at baseline. In contrast, abstainers showed a significant negative association of the ventromedial PFC with the visual cortex. The increased across-community interaction of the ventromedial PFC and the visual cortex in relapsers at timepoint 1 may be an early indicator for treatment failure in a subgroup of AUD patients.